Tomb architecture and distribution in the eastern necropolis of NEA Paphos, Cyprus - Lysandrou, Vasiliki (My University, 2020)
The Eastern necropolis of Nea Paphos is one of the most significant funerary landscapes of Cyprus, primarily because of its connection with the capital of the island during the Hellenistic and Roman times, and therefore of importance for the archaeology of the Eastern Mediterranean. The first systematic exploration of the site took place in the 1980s in the form of rescue excavations. Only limited research has been undertaken since then. This article discusses the necropolis based on unpublished material from the rescue excavations. It presents the tombs' architecture; partially reconstructs the burial ground; reveals the extension of the necropolis; triggers questions related to the dynamics between nearby necropolis, and its potential correlation to satellite habitation sites.
Keywords: Tomb architecture; Eastern necropolis of Nea Paphos; Legacy data; GIS; Cyprus